IbM PELATIHAN MENGGUNAKAN APLIKASI ANIMASI BELAJAR BACA TULIS HURUF HIJAIYYAH PADA TK/TPA KHAIRUL ANAM MAKASSAR - Rosnani; Dikwan Moeis; Musdalifah (PROGRESS, 2016)
TK / TPA Khoirul Anam is one of the Education Park Qur'an (TPA) or TPQ, the most basic level of education. It aims to educate, teach and inculcate the pupils in reading the Qur'an tartil. The applied learning system still uses a conventional system that is Uztad and Ustadzah teaches directly from recognizing hijaiyah letters of the Iqro book volume 1 to volume 6, with a direct reading method, CBSA (Active Student Learning Method).IbM team introduced a method of learning to read the letters of hijaiyah by using Animation Application Program. Its objectives were (1) To help the teachers and pupils in the process of learning to read the letters of hijjaiyyah by using animation applications. (2) To improve the skills of pupils in reading letters hijaiyyah by using animation applications. The learning method used a lecture and demonstration methods.The training activities lasted in 300 minutes (5 hours). The first part of the training was to demonstrate the animation application wherein each part consisted of 4 levels, each level based on the level of reading on Iqro 1 to Iqro 6.The pupils had a test before teacher explained the subject about how to read the letters of hijaiyyah by using animation application. After the training was conducted, the pupils had a test again to determine the effectiveness of the animation application which was able to be absorbed by the pupils. From the data of 15 respondents were then asked questions, the ability of respondents who answered the question with the correct answers were 12 pupils. There were 80% of pupils who answered questions correctly. There were 3 respondents from 15 respondents who answered the questions with the wrong answers. It means that there were 20% of pupils who were not able to answer the questions correctly.